Understanding Snake Bite Cases Pattern Related to Volcano-Seismic Activity: An Evidence in Bondowoso, Indonesia - Nia Kurniawan; Ahmad Muammar Kadafi; Agung Sih Kurnianto; Franky Ardiansyah; Tri Maharani (Biotropika: Journal of Tropical Biology, 2017)
Bondowoso located in a valley of Raung mountain roots in East Java, Indonesia. The eruption of Mt. Raung in 2015 not only cause loss of life, but also underlining the fact of unusual Snake Bite Cases (SBC), as recorded in the dr. Koesnadi Hospital. We conducted a thorough analysis of the SBC in 2015 along with the survey on all the incident location in January to March 2016. This study represented an improvement on the population of venomous snake in the agriculture area, and reached the highest peak before the eruption. The presence of continuous vegetation at the edge of watersheds become green corridor that functioned as the movement track for snakes in order to avoid the volcano effect.